Quantum dot-decorated silicon nanowires as efficient photoelectrodes for photoelectrochemical hydrogen generation - Devarapalli, Rami Reddy; Kamaja, Chaitanya Krishna; Shelke, Manjusha V. (Journal of Materials Chemistry A, 2014)
Quantum dot-decorated wide band gap semiconductors, such as TiO2, ZnO, SnO2, etc., which have electron mobilities of less than 200 cm(2) V-1 S-1 have been well studied as the photoelectrodes for photovoltaics and photoelectrochemical water splitting. Herein, we report CdSe quantum dot decorated-silicon nanowires (SiNWs) as photoelectrodes for photoelectrochemical water splitting. SiNWs have a comparatively higher electron mobility than metal oxides. A photocurrent density of around 6.1 mA cm(-2) was obtained for the CdSe/SiNWs photoelectrode, which is nearly five times higher than that for SiNWs alone and which also shows a good transient photocurrent response. The band energy level alignment was also studied between Si and CdSe by observing the corresponding flat band potentials from a Mott-Schottky analysis.